PP.08.09: PULMONARY ARTERIAL HYPERTENSION IN INTERNAL MEDICINE DEPARTMENT. (June 2015) - Rachdi, I.; Daoud, F.; Aydi, Z.; Baili, L.; Dhaou, B. Ben; Boussema, F.
Abstract : Objective: Despite progresses in the knowledge of pulmonary arterial hypertension (PAH) pathophysiology, it is still a devastating disease needing an aggressive approach of therapy to improve long-term outcomes. The purpose of our study is to describe prognostic and therapeutic characterics. of PAH in internal medicine department Design and method: A retrospective study over a period of 14 years (2000–2014) concerning patients admitted in internal Medicine department for PAH. Pulmonary arterial pressure (PAP) was estimated from the data of cardiac ultrasound Doppler. A PAH was retained in front of PAH superior to 30 mmHg. Results: Fourty-six patients were retained. Middle age of patients was of 60, 6 years (24–48 years). Middle age of diagnosis of PAH was of 48, 3 years. Main causes of PAH were connective tissue diseases (CTD) in 24 patients (52, 1 %). PAH was secondary to thrombo-embolic disease at 9 patients (19, 5%), to left heart disorders at 6 patients (13%). PAH was associated to hypoxemic respiratory affection in a case, to a hyperthyroidism in a case and to acute myeloid leukemia in an another case. An idiopathic PAH was retained at 9%. All patients received symptomatic treatment (anticoagulants). Calcic inhibitors were prescribed in 25 patients (54%). Among them, twenty four patients had CTD. Specific treatment was prescribed using prostacycline at 2 patients and an antagonist of the receivers of the endotheline in 3 other patients with ScS An etiological treatment using corticosteroids and cyclophosphamide boluses, was instaured in 8 cases with SLE or SLE ScS overlap syndrome. In all patients receiving cyclophosphamide boluses or specific treatment (Benzylthiouracile, anticoagulants), we noted an improvement of PAP. A worsening was noted in 8 cases (17%), in a patient with hypoxemic respiratory disease, two with left heart disorders and five with ScS or ScS-SLE overlap syndrome. Average duration of follow-up was of 47 months. A single death was noted due to global cardiac insuffiency in a patient with ScS. Another death was noted in patient with acute myeloid leukemia. Conclusions: The prognosis of PAH is better when using specific treatments. Immunosuppressive treatment could be useful in mild to moderate PAH associated to systemic lupus and mixed connective tissue disease.